A separation principle of time‐varying dynamical systems: A practical stability approach - Ellouze, Ines (Mathematical Modelling and Analysis, 2007)
In this paper we treat the problem of practical feedback stabilization for a class of nonlinear time‐varying systems by means of an observer. A separation principle is given under a restriction about the perturbed term that the perturbation is bounded by an integrable function where the nominal system is supposed to be globally asymptotically stabilizable by a linear feedback. A practical stability approach is obtained. Furthermore, we give an example to show the applicability of our result.First Published Online: 14 Oct 2010